The Legal Consequences of Informed Consent for Doctors and Patients in Theurapeutic Agreements - Iip Verra Selvia; Arief Suryono; Sapto Hermawan (Aloha International Journal of Health Advancement (AIJHA), 2020)
Informed consent is a requirement for the occurrence of therapeutic agreements between doctors and patients. Therapeutic agreements are agreements where healing effort (inspanningverbittenes) is constituted as legal object. A patient who has given a consent is considered to understand the benefits and risks of medical treatment he would receive. However, the existence of informed consent does not make any doctor immune to the law. If a doctor works outside the professional standards and operational standards that apply and is proven by the professional association, then a doctor could be sanctioned according to applicable regulations. On the other hand, the patient is required to be cooperative in providing information and complying with the medical procedures. The existence of a therapeutic agreement results in both doctor and patient being bound to each other's rights and obligations. Keywords: informed consent; therapeutic agreement; doctor; patient